2000
DOI: 10.1074/jbc.m001478200
|View full text |Cite
|
Sign up to set email alerts
|

Human NRAMP2/DMT1, Which Mediates Iron Transport across Endosomal Membranes, Is Localized to Late Endosomes and Lysosomes in HEp-2 Cells

Abstract: NRAMP2 (natural resistance-associated macrophage protein 2)/DMT1 (divalent metal transporter 1) is a divalent metal transporter conserved from prokaryotes to higher eukaryotes that exhibits an unusually broad substrate range, including Fe 2؉ , Zn 2؉ , Mn 2؉ , Cu 2؉, Cd 2؉ , Co 2؉ , Ni 2؉ , and Pb 2؉ , and mediates active proton-coupled transport. Recently, it has been shown that the microcytic anemia (mk) mouse and the Belgrade (b) rat, which have inherited defects in iron transport that result in iron deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
167
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(188 citation statements)
references
References 40 publications
19
167
1
Order By: Relevance
“…The amino acid sequence of DMT should result in a molecular weight of about 60 kD. Other investigators have identified the presence of a large molecular weight form, about 90 kD, and shown that this was due to extensive glycosylation [19,20]. Treatment of the DMT-1 bound to the mucin fraction with glycosidase-P (Fig.…”
Section: Dmt-1 Associated With Mucin Is In the Glycosylated Formmentioning
confidence: 92%
“…The amino acid sequence of DMT should result in a molecular weight of about 60 kD. Other investigators have identified the presence of a large molecular weight form, about 90 kD, and shown that this was due to extensive glycosylation [19,20]. Treatment of the DMT-1 bound to the mucin fraction with glycosidase-P (Fig.…”
Section: Dmt-1 Associated With Mucin Is In the Glycosylated Formmentioning
confidence: 92%
“…4 DMT-1 has been detected also in the endosomal compartment of different cells, suggesting that it participates in the transport of transferrin (Tf)-bound iron across the cellular membrane of acidified endosomes, resulting in the release of iron into the cytoplasm. 5,6 After entering enterocytes, iron is used for essential metabolic purposes, stored in ferritin or translocated to …”
mentioning
confidence: 99%
“…4 DMT-1 has been detected also in the endosomal compartment of different cells, suggesting that it participates in the transport of transferrin (Tf)-bound iron across the cellular membrane of acidified endosomes, resulting in the release of iron into the cytoplasm. 5,6 After entering enterocytes, iron is used for essential metabolic purposes, stored in ferritin or translocated to the portal blood by ferroportin-1 (Fpn-1). The plasma protein, Tf, binds to diferric iron (Fe 2 Tf) and transfers it through portal blood to the liver, where either the Tf receptor-1 (TfR1) 7 or Tf-independent mechanism mediates hepatic uptake of iron.…”
mentioning
confidence: 99%
“…Although the two isoforms of DMT1 produced by alternative splicing are both present at the plasma membrane, the difference in the subcellular localization appears to be dependent upon cation needs. The +IRE isoform is found mainly at the apical membrane of epithelial cells Courville et al, 2006) and late endosomes and lysosomes within HEp-2 cells (Tabuchi et al, 2000;Lam-Yuk-Tseung et al, 2005b). On the other hand, -IRE isoforms are found predominantly in early and recycling endosomes Kannurpatti et al, 2000;Touret et al, 2003).…”
mentioning
confidence: 99%